THE INFLUENCE OF E-SERVICE QUALITY AND BRAND IMAGE ON CUSTOMER LOYALTY THROUGH CUSTOMER SATISFACTION ON 'BIBIT' APPLICATION USERS - Ellitan, Lena; Lim, Sisilia Felicia; Kristanti, Maria Mia (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2023)
Currently, it is undeniable that advances in science and technology have an impact on people's lifestyles. One of them can be seen in investing activities that can be done only by having a smartphone and an internet network. Business actors use this situation to provide mutual fund investment applications. It is characterized by increasing competition between mutual fund investment applications. Increased public awareness of the importance of investment is an added value. One of the mutual fund investment applications known to be on the rise is Bibit. This study examines the effect of e-service quality and brand image on customer loyalty through customer satisfaction on users of the Bibit application. The sampling technique used is non-probability sampling with a purposive sampling type. The sample used is 150 respondents who are users of the Bibit application. The data analysis technique used is PLS-SEM with SmartPLS 3.0 program. The results showed that e-service quality and brand image each had a positive and significant effect on customer satisfaction, e-service quality and customer satisfaction each had a positive but not significant effect on customer loyalty brand image had a positive and significant effect. Customer loyalty and customer satisfaction proved unable to mediate the effect of e-service quality and brand image on customer loyalty.